Design and analysis of 73-106 GHz CMOS injection-locked frequency divider. Issue 4 (3rd April 2021) - Lin, Yo-Sheng; Lan, Kai-Siang; Wang, Chih-Wei
ABSTRACT: A 73 106 GHz divide-by-2 injection-locked frequency-divider (ILFD2) using 90 nm CMOS technology is presented. To achieve a wide locking range, an optimal transistor width ratio of the injection transistor (or mixer) and cross-coupled transistors (CCT) is adopted. To enhance the operation frequency, distributed LC network is used as the load of the CCT. To enhance the input sensitivity, an input power matching network is included in the injection transistor. In addition, for further locking ranging enlargement, the inductive peaking and forward-body-bias techniques are used in the injection transistor for raising its quadrature output current (or conversion gain). The ILFD2 consumes 4.92 mW, and achieves an excellent phase noise of – 106.2 dBc/Hz (at 1 MHz offset from the output frequency of 50 GHz). The ILFD2 achieves a wide locking-range of 33 GHz (73–106 GHz (36.9%)), covering the 77 GHz automotive radar frequency band and the 94 GHz imaging radar frequency band. The ILFD2 can be operated at a low input power of – 60 dBm, one of the best input sensitivities ever reported for a W-band CMOS ILFD2. The core area of the ILFD2 is only 0.014 mm 2 .